Perilaku Harian Rusa Timor (Rusa timorensis) di Stasiun Penelitian Bu’at Kecamatan Mollo Selatan, Kabupaten Timor Tengah Selatan, Provinsi Nusa Tenggara Timur - Lay, Victor Y.; Riwu Kaho, Ludji Michael; Riwu Kaho, Norman P.L.B. (Wana Lestari, 2022)
A study that aims to determine the daily behavior of the Timor deer (Rusa timorensis) at the Bu'at Research Station, South Mollo District, South Central Timor Regency, East Nusa Tenggara Province; and to find out the daily behavior comparison between Timor deer (Rusa timorensis) individuals based on sex and age (adult male, adult female, male child and female child) at the Bu'at Research Station, South Mollo District, South Central Timor Regency, Nusa Tenggara Province. East from October - December 2019. The method used is the scan sampling method and the object of research is one adult male individual, one adult female individual, one male juvenile individual, and one female juvenile individual. The results of the study were ingestive/eating behavior (38.23%); resting/resting behavior (28.54%); locomotion/walking behavior (29.27%), vocalization/voice behavior (1.46%), eliminative behavior/pooping (0.61%); social behavior (1.82%); sexual behavior (0%); and other behaviors (0.07%); and the comparison of daily behavior between individuals of Timor deer (Rusa timorensis) which were significantly different were adult male deer and juvenile female deer on locomotion (walking) behavior. While in ingestive behavior, resting behavior, vocalization behavior, eliminative behavior, social behavior, and sexual behavior there are no significant differences or can be considered the same